Epigallocatechin-3-gallate supplementation can improve antioxidant status in stressed quail - Tuzcu, M.; Şahin, Nurhan.; Karatepe, M.; Cikim, G.; Kilinc, U.; Şahin, Kazım (Taylor & Francis Ltd, 2008)
1. Heat stress causes oxidative stress, which decreases plasma antioxidants in poultry. Epigallocatechin gallate (EGCG), the most abundant polyphenol in green tea, is a powerful antioxidant against lipid peroxidation. This experiment was conducted to evaluate the effects of dietary EGCG supplementation on performance, carcase characteristics, concentrations of malondialdehyde, lipid peroxidation indicator, vitamins C, E, A, cholesterol, triglyceride, and glucose in Japanese quail (Coturnix coturnix japonica) exposed to a high ambient temperature of 34 degrees C. 2. One hundred and eighty Japanese quails (10 d old) were assigned at random to 6 treatment groups consisting of 10 replicates of three birds. Birds were kept in cages in a temperature-controlled room at either 22 degrees C (thermo-neutral) or 34 degrees C (heat stress) for 8 h/d. Birds were fed either a basal diet or the diet supplemented with 200 or 400 mg of EGCG/kg of diet. 3. EGCG supplementation linearly increased feed intake, live weight gain, feed efficiency, cold carcase weight and yield under heat stress conditions but did not show the same effect at thermoneutral conditions. Serum vitamin C, E, and A concentrations increased in birds reared at high temperature while non-significant changes occurred in thermo-neutral groups. Malondialdehyde concentrations in serum and liver decreased in all birds of both thermo-neutral and heat stressed groups as dietary EGCG supplementation increased. Heat stress-induced increase in serum cholesterol, triglycerides and glucose concentrations were linearly reversed by EGCG supplementation. 4. The results indicate that EGCG supplementation improved the live performance and antioxidant status of heat-stressed Japanese quail.
Keywords: Lipid-Peroxidation; Green Tea; Vitamin-E; (-)-Epigallocatechin Gallate; Mineral Concentrations; Radicals; Serum; Inhibition; Growth